Biphasic dissolution method for quality control and assurance of drugs containing active substances in the form of weak acid salts - Franc Aleš; Muselłk Jan; Goněc Roman; Vetchý David (Acta Pharmaceutica)
Substances in the form of weak acid salts have been found to be problematic for dissolution testing. Their absorption can start only after they are turned into the form of an acid following the gastric passage although they were administered in the form of a salt. Due to poor solubility, they cannot be tested in acidic gastric environment for a biased dissolution profile. The biphasic dissolution method is promising for overcoming this obstacle. Tablets with warfarin clathrate sodium salt in two concentrations and two different particle size distributions were tested as a suitable model for finding the medium and process conditions of dissolution. The dissolution method based on the use of the upper organic layer (1-octanol) and the lower aqueous layer 0.1 mol L−1 HCl) was found suitable and discriminatory for tablets containing active substances in the form of salts of weak acids. The method also reflects physical differences in the quality of used substances.